Palm kernel shell, nanosilica and palm kernel shell / nanosilica filled polypropylene hybrid composites - Muhammad Safwan Mohaiyiddin (School of Materials Engineering, Universiti Malaysia Perlis, 2011)
The purpose of this research is to prepare and characterize palm kernel shell / nano SiO2 filled polypropylene hybrid composites are to: i- determine the optimum loading palm kernel shell(PKS) in polypropylene in order to achieve good balance in mechanical properties and water absorption properties. ii- determine the optimum loading of nanosilica in polypropylene in order to achieved good balance in tensile strength. iii- study the hybriding effect on the mechanical properties, thermal properties and water absorption properties of polypropylene composites. iv- study the effect of polypropylene grafted maleic anhydride (PPMAH) on the mechanical properties, thermal properties and water absorption properties of PKS / nanosilica filled polypropylene hybrid composites.